The importance of using the peripherally inserted central cateter (Research, Society and Development, 2020)
Objective: The PICC peripherally inserted central venous catheter is a catheter that inserts into a peripheral vein and progresses to the superior or inferior vena cava, acquiring the characteristics of a central catheter. It is a device that has several versions, with one, two or three lumens, it is flexible, radiopaque, with smooth and homogeneous walls, made of silicone or polyurethane. Such a device benefits in the treatment of newborns who require long-term care. This study aims to analyze the importance of using the Peripherally Inserted Central Catheter - PICC in the care of sick neonates, as well as to analyze the role of the nursing team in the insertion and maintenance of this technique. The methodology used was bibliographic research with analysis of scientific articles, theses and other nursing publications found in databases related to the theme. The results from the studies reviewed showed that PICC is a device arising from new technologies that provide better treatment to newborns who need prolonged treatment. The nurse and the nursing team must always be updated and trained to provide humanized and quality care.